The Scenario of organ and Tissue Donation for Post-mortem Transplantation in the 16th Health Region/RS - Silva, Isadora Cristina da (2023)
Introduction: The donation and transplantation of organs and tissues is a topic of multiprofessional interest and an important theme regarding the promotion of public health policies regarding the application of this therapy. Objectives: The objective of this article is to present an analysis of the scenario of organ and tissue donation after death, for transplantation, in the 16th Health Region of Rio Grande do Sul between 2010 and 2020, focusing on evaluating family refusals to donate. Methods: A census survey was carried out of the data referring to the brain death protocols carried out in the period, tabulated in Microsoft Excel, analyzedthrough the construction of time series and related using the chi-square test. Results: The analysis in the region shows a higher proportion of negatives (57.8 %) concerning acceptances (42.2 %) for organ and tissue donation. However, when only the last years of the period are observed, another reality is seen: from 2017 to 2019, the donation statements corresponded to more than 75% of the interviewed families. In 2020, however, in an atypical way, no brain death protocols were concluded; therefore, no family underwent the interview for donation. Conclusion: There has been a trend toward an increase in donation percentages over the years, both in the 16th Health Region of Rio Grande do Sul and the rest of the country. However, the number of transplants performed is still lower than the population’s need.